The Effect of Party Affiliation on Developing Awareness of Social Policies among Members of the General Bodies of Parties in Karak Governorate - Al Majali , Alaa (Jordan Journal of Social Sciences, 2024)
The research aimed to measure the impact of party membership on raising awareness of social policies among the general assembly members of political parties in the Karak Governorate. To achieve the research objective, the descriptive-analytical method was adopted, using a questionnaire as the data collection tool. The research sample consisted of 213 party members in the Karak Governorate. The results showed that there is an impact of party membership on raising awareness of social policies among the general assembly members of political parties in Karak, with a high level of influence. The development of political awareness ranked first, at a high level, and the methods used ranked last, also at a high level. The results also indicated no statistically significant differences in the responses of the study sample based on gender, educational qualification, or age. However, differences were found related to the duration of membership, showing that the perceptions of the study sample toward the impact of party membership on raising awareness of social policies varied between those with less than two years of membership and those with more than four years, with the latter group showing a higher level of awareness. The researcher recommended that responsible authorities provide financial and moral support to political parties to enhance their positive role in raising awareness of social policies. It was also suggested that parties should hold training and qualification courses for all members, especially new ones, and focus on highlighting the role of parties in raising awareness of social policies.